Contributions of Inflammatory Processes to the Development of the Early Stages of Diabetic Retinopathy. (30th September 2007) - Kern, Timothy S.
Abstract : Diabetes causes metabolic and physiologic abnormalities in the retina, and these changes suggest a role for inflammation in the development of diabetic retinopathy. These changes include upregulation of iNOS, COX-2, ICAM-1, caspase 1, VEGF, and NF-κ B, increased production of nitric oxide, prostaglandin E2, IL-1β, and cytokines, as well as increased permeability and leukostasis. Using selective pharmacologic inhibitors or genetically modified animals, an increasing number of therapeutic approaches have been identified that significantly inhibit development of at least the early stages of diabetic retinopathy, especially occlusion and degeneration of retinal capillaries. A common feature of a number of these therapies is that they inhibit production of inflammatory mediators. The concept that localized inflammatory processes play a role in the development of diabetic retinopathy is relatively new, but evidence that supports the hypothesis is accumulating rapidly. This new hypothesis offers new insight into the pathogenesis of diabetic retinopathy, and offers novel targets to inhibit the ocular disease.